A partial length cyclophilin-encoding (cyp) cDNA isolated from Ganoderma boninense - Lim, Fook Hwa; Iskandar, Nor Fakhrana; Shaharuddin, Noor Azmi; Abd Rasid, Omar; Abu Seman, Idris; Ghulam Ahmad, Ahmad Parveez (Malaysian Palm Oil Board, 2011)
Oil palm is subjected to various pests and diseases, one of the most important being basal stem rot (BSR) disease which is caused by a few species of Ganoderma. Ganoderma is a white rot fungus that attacks oil palm around the world. During plant infection, a few genes are highly expressed in the fungus and have been linked to fungal pathogenicity. One of these genes is the cyclophilin-encoding gene (cyp). In this study, degenerate primers have been designed based on the conserved regions of the gene. PCR amplification successfully amplified a 212 bp DNA fragment from Ganoderma boninense cDNAs. The DNA sequence analysis showed that the fragment has about 80% similarity to other plant pathogenic fungal cyp genes. The translated amino acid sequence was also highly identical to other plant pathogenic fungal cyclophilin. Conserve domain search results show that the obtained sequence has similarity to the cyclophilin_ABH-like domain.